ANALYSIS OF THE INFLUENCE OF COMPANY PROFITABILITY, LEVERAGE AND SIZE ON TAX AVOIDANCE ACTIONS PERFORMED BY COMPANIES DURING THE COVID-19 PANDEMIC ON TRANSPORTATION COMPANIES IN BEI - Getrudis Naldis; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
Tax avoidance is one way to reduce the tax burden in a legal way. This study aims to examine and analyze the effect of financial factors, namely profitability, leverage, and company size on tax avoidance during the Covid-19 pandemic. This research belongs to the type of quantitative research using secondary data from the financial statements of the first, second, and third quarters. The population of this study is 43 transportation sector companies listed on the Indonesia Stock Exchange (IDX) in 2020. The research sample was selected using a purposive sampling method which then obtained a sample of 33 data from 11 companies during the first, second, and third quarters of 2020. Data analysis using multiple regression equation analysis technique.